Innovation and Development India as an Example - VIJAYA L. MELNICK and DANIEL MELNICK (Comparative Technology Transfer and Society, volume 5, number 2 (August 2007):202-23, 2007)
Innovation is the key to transforming people's lives. Scientific research and novel technologies deliver real benefits only when innovators appropriately apply them to improve the lives of ordinary people. Innovative approaches anchored in the local context assume a truly transformative power. This essay discusses the role of innovation in development and uses examples from India that illustrate how that country has facilitated innovation to transform how people live, work, and overcome problems bydrawing upon critical resources. Changed values and decisions- highly personal and specific factors-emerge as key. These innovations critically involve the diffusion of new ideas and their acceptance by new users. Innovation and technology transfer are vital elements in this story. Examining how innovations are implemented reveals the tension between national advances and delivering the benefits of change to all parts of Indian society. Making technology accessible to a wider Indian public involves the diffusion of new approaches, th e internalization of new ideas, and transfer of these approaches from the technological cadre that is a product of India's elite scientific and technical institutions to the broader public. The essay describes a number of efforts to disseminate advances to disadvantaged groups and to involve them in the development process. The questions that remain are: Will this effort be sufficient to retain the support of Indians for advances that demand change and a renewed commitment to excellent efforts? What is the appropriate balance between growth and social justice? Clearly, these are issues that the current Indian government has at the top of its agenda